2002
DOI: 10.1182/blood-2002-04-1033
|View full text |Cite
|
Sign up to set email alerts
|

Host defense and inflammatory gene polymorphisms are associated with outcomes after HLA-identical sibling bone marrow transplantation

Abstract: We made the hypothesis that donor and recipient gene polymorphisms that drive the host response to microorganisms could be associated with infections after bone marrow transplantation (BMT). HLAidentical BMT was performed for patients with acute (n ‫؍‬ 39) or chronic leukemia (n ‫؍‬ 68). Univariate and multivariate analyses, using death as a competing event, were performed to study risk factors. In multivariate analysis, first overall infections were increased in patients with the Fc␥RIIa R-131 genotype (hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
139
5
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(153 citation statements)
references
References 65 publications
6
139
5
3
Order By: Relevance
“…Donations of livers (the main MBL source) from variant donors to wild-type recipients resulted in rapidly decreasing MBL serum levels. 21 This is in line with earlier studies 22 in which donors' genotypes did not influence transplant-related complications. Therefore, it is unclear how to explain the findings of Mullighan et al and Granell et al 10,12 that transplantation outcome depended on MBL genotypes of both recipients and donors.…”
Section: Discussionsupporting
confidence: 81%
“…Donations of livers (the main MBL source) from variant donors to wild-type recipients resulted in rapidly decreasing MBL serum levels. 21 This is in line with earlier studies 22 in which donors' genotypes did not influence transplant-related complications. Therefore, it is unclear how to explain the findings of Mullighan et al and Granell et al 10,12 that transplantation outcome depended on MBL genotypes of both recipients and donors.…”
Section: Discussionsupporting
confidence: 81%
“…11,12 An association of MBL deficiency and infection is also reported in patients treated with conventional chemotherapy 13,14 or high-dose myeloablative chemotherapy followed by allogeneic stem cell transplantation, 15 which is not confirmed by others. 16,17 In the present study, we report an increased risk of major bacterial infection in patients carrying the MBL polymorphism when treated with high-dose chemotherapy (HDT) followed by autologous peripheral blood stem cell transplantation (auto-PBSCT). In addition, the allele frequencies of the MBL polymorphism in a total of 2623 healthy individuals were determined in seven different areas in Japan, which is, to our knowledge, the largest scale of study for MBL polymorphism in a single ethnic group.…”
mentioning
confidence: 73%
“…It has recently been demonstrated that MBL deficiency is a genetic risk factor of infection in patients treated with HDT and allogeneic stem cell transplantation, 15 which was not confirmed by others. 16 As a variety of complex factors other than MBL polymorphism such as the effect of donor cells should be considered in allogeneic stem cell transplantation, HDT and auto-PBSCT will provide a clearer model to analyze the contribution of MBL polymorphisms to infection after myeloablative treatments. The condition with more reduced dose of chemotherapy, conventional-dose chemotherapy without stem cell support, has been demonstrated to be at an increased risk of infection or prolonged fever in several reports, 13,14 but not by others.…”
Section: Increased Risk Of Infection In Mbl Polymorphismmentioning
confidence: 99%
“…27,28 Two previous studies failed to find an association between the TNFB þ 252 polymorphism and aGVHD. 29,30 The results of this study provide the first evidence that TNFB þ 252 G allele-positivity of recipients and/or donors was associated with an increased susceptibility to aGVHD in a Chinese population. The role of TNF-b in aGVHD is much less well known than that of TNF-a.…”
Section: Discussionmentioning
confidence: 72%